2009
DOI: 10.1007/s00464-008-0303-4
|View full text |Cite
|
Sign up to set email alerts
|

Minimally invasive video-assisted thyroidectomy compared with conventional thyroidectomy in a general surgery department

Abstract: The MIVAT technique, in selected patients, seems to be a valid option for thyroidectomy and even preferable to conventional surgery because of its significant advantages, especially in terms of cosmetic results, postoperative pain, and postoperative recovery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 14 publications
0
21
0
Order By: Relevance
“…Fiftyseven relevant thyroidectomy papers were identified, twenty of which reported some form of cosmetic outcome assessment. These included 6 randomised controlled trials (RCTs) with 412 patients (evidence level 2B), [6][7][8][9][10][11] 7 cohort studies with 3,073 patients (level 3B) [12][13][14][15][16][17][18] and 7 non-comparative case series with 1,575 patients (level 4). [19][20][21][22][23][24][25] The remaining studies made reference to the issue of cosmesis either by assumption, referencing or general statements unsupported by methodological assessment.…”
Section: Review Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Fiftyseven relevant thyroidectomy papers were identified, twenty of which reported some form of cosmetic outcome assessment. These included 6 randomised controlled trials (RCTs) with 412 patients (evidence level 2B), [6][7][8][9][10][11] 7 cohort studies with 3,073 patients (level 3B) [12][13][14][15][16][17][18] and 7 non-comparative case series with 1,575 patients (level 4). [19][20][21][22][23][24][25] The remaining studies made reference to the issue of cosmesis either by assumption, referencing or general statements unsupported by methodological assessment.…”
Section: Review Resultsmentioning
confidence: 99%
“…13,16,18 All four cohort studies containing MIVAT in one arm found this to be cosmetically superior to CT but this only reached statistical significance in three of the studies, 14,15,17 none of which used a validated assessment tool at >6 months postoperatively. The single study that used a validated assessment tool (body image questionnaire) at six months found no significant cosmetic advantage to MIVAT.…”
Section: Cohort Studiesmentioning
confidence: 98%
See 1 more Smart Citation
“…This alteration allows it to be adopted by low-volume surgeons, unlike other minimal access thyroid procedures that are only embraced by high-volume centers. An adequate learning curve and the use of re-usable instruments allow MIVAT to be performed at a cost comparable to that of CT (21,22) and with no significant added operative time (23)(24)(25). Although it has been reported that MIVAT requires a significantly longer time to perform in comparison to CT (7), the authors' vast experience with the procedure has demonstrated its comparability to CT in operative time.…”
Section: Learning Curve Operative Time and Costmentioning
confidence: 99%
“…On the second day after the surgery, the aspiration drain was removed. Postoperative pain was assessed by means of a visual analog scale (VAS), which consisted of a 10‐cm line with the words “no pain” on the left side at zero and “worst pain imaginable” on the right side at 10 …”
Section: Case Reportsmentioning
confidence: 99%